Deprivation: Endowment and Discrimination? - Yilmaz, Ensar; Kilic, Ibrahim Engin (SPRINGER, 2021)
Due to the lack of good-quality data, there has been no sound research about the economic welfare of the Romani in the countries where they live. Drawing on a comprehensive survey conducted on the economic welfare of the Romani people in Turkey, we employed multidimensional poverty measures to capture the structural side of the poverty of the Romani in Turkey, in a comparative manner with the non-Romani majority. The paper also decomposes the determinants of the multidimensional poverty. This helps us to identify the structural, personal characteristics and discrimination components of the poverty. This simultaneously allows us to comprehend the endowment and discrimination effects of different income layers of both groups.
Keywords: Romani; Multidimensional poverty; Poverty gap; Discrimination; Social Sciences - Other Topics; Sociology